Assessment of genetic variability, correlation and path association in rice (oryza sativa l.) - Yadav, SK; Suresh, BG; Pandey, Praveen; Kumar, Binod (Journal of Bio-Science, 2011)
Context: Direct selection based on crop yields is often a paradox in breeding programmes because yield is a complex polygenically inherited character, influenced by its component traits. Objectives: The present research work was taken up to assess genetic variability, phenotypic and genotypic associations between various components of grain yield to provide basis for selection and yield improvement in rice. Materials and Methods: Correlation coefficient and path association are used to find out the degree (strength) and direction of relationship between two or more variable and for fixing up the characters which are having decisive role in influencing the yield. Therefore, a field experiment was carried out to establish the extent of association between yield and yield components and others characters in rice. Analysis of variance revealed that significant amount of genetic variability was present in the entire characters studied. Results: High heritability coupled with high to moderate genetic advance as % of mean was observed on plant height seed yield per plant, biological yield, harvest index, test weight and number of spikelets per panicle suggesting preponderance of additive gene action in the expression of these characters. The correlation coefficient between seed yield per plant and other quantitative attributing to yield showed that grain yield was significantly and positively associated with harvest index, number of tillers per hill, number of panicle per plant, panicle length, number of spikelet's per panicle and test weight at both genotypic and phenotypic levels. Path coefficient at genotypic level revealed that harvest index, biological yield, number of tillers per hill, panicle length, number of spikelets per panicle, plant height and test weight had direct positive effect on seed yield per hill, indicating these are the main contributors to yield. Conclusion: From the correlation and path study it may be concluded that harvest index, number of tillers per hill, panicle length, and number of spikelet per panicle and test weight are the most important characters that contributed directly to seed yield per hill. Thus a genotype with higher magnitude of these traits could be either selected from existing genotypes or evolved by breeding program for genetic improvement of yield in rice. Key words: Rice; variability; heritability; agro-morphological traits; correlation; path DOI: http://dx.doi.org/10.3329/jbs.v18i0.8767 JBS 2010; 18(0): 1-8